Bodies of transnational island urbanism: Spatial narratives of inclusion/exclusion of Filipinas in Philippine islands. (December 2022) - Ortega, Arnisson Andre C
Tropical islands can become terrains of urbanisation worthy of examination. In the Philippines, several islands have experienced urban transformation (capital accumulation, immigration, diversification, land conversion) through tourism. At the forefront of these urban transformations are Filipinas, particularly those in interracial relationships with foreign men who invest in island properties and establish resorts. These resorts stimulate a transnationally-oriented mode of urban transformation reliant on the transnational mobilities of tourists, expats and capital. This paper examines this by foregrounding the experiences of Filipinas, concentrating on how they are differentially included and excluded throughout the multi-scalar process of island urban accumulation. I locate these differential experiences in various spaces (nation, community, resort, households), noting in particular the (1) national discourses underlying state tourism and foreign retirement programmes, (2) transactions enabling property purchases and resorts, and (3) translocal mobilities sustaining urban accumulation. What emerge from these accounts are the selective inclusions and exclusions of Filipinas in transnational urban accumulation in the islands. While their role in facilitating island urban accumulation may suggest a form of 'empowered' inclusivity, this can easily be undercut by sexist micropolitics of exclusion that tend to reduce them to 'mere women' and/or 'prostitutes'. Such differential practices of inclusion/exclusion demonstrate the gendered dynamics that unequally put a double burden on Filipinas. Unravelling these accounts demonstrates how gendered relations and sexuality are important forces underpinning urban transformation and transnational mobilities that constitute diversification.